2018
DOI: 10.3892/br.2018.1044
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide insufflation reduces residual gas in the gastrointestinal tract following colorectal endoscopic submucosal dissection

Abstract: Abstract. Quantitative examinations evaluating the effects of CO 2 insufflation on residual gas in the gastrointestinal tract following colorectal endoscopic submucosal dissection (ESD) are lacking. The present study aimed to assess whether CO 2 insufflation could decrease the amount of residual gas in the gastrointestinal tract following ESD in patients with colorectal neoplasms. Computed tomography (CT) was used to objectively examine whether CO 2 insufflation during colorectal ESD reduced residual gas level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Although the use of CO2 insufflation has been demonstrated to be safe for use during colorectal ESD in patients under sedation, even in the setting of obstructive pulmonary diseases, few comparative studies have demonstrated its clinical impact (Table 7 s) [180,181]. In an RCT, CO2 insufflation significantly reduced residual gas in the gastrointestinal tract following colorectal ESD as compared to air insufflation (P < 0.001); this outcome was thought to be associated with less discomfort, although the incidence of ESD-related complications did not differ between groups [182]. An earlier systematic review and meta-analysis has shown that insufflation with CO2 in colonoscopy reduced abdominal discomfort during and after the procedure without any adverse reactions [183].…”
Section: Colonmentioning
confidence: 99%
“…Although the use of CO2 insufflation has been demonstrated to be safe for use during colorectal ESD in patients under sedation, even in the setting of obstructive pulmonary diseases, few comparative studies have demonstrated its clinical impact (Table 7 s) [180,181]. In an RCT, CO2 insufflation significantly reduced residual gas in the gastrointestinal tract following colorectal ESD as compared to air insufflation (P < 0.001); this outcome was thought to be associated with less discomfort, although the incidence of ESD-related complications did not differ between groups [182]. An earlier systematic review and meta-analysis has shown that insufflation with CO2 in colonoscopy reduced abdominal discomfort during and after the procedure without any adverse reactions [183].…”
Section: Colonmentioning
confidence: 99%